Cell wall protection by the Candida albicans class I chitin synthases - Kanya Preechasuth (2018)
© 2015 The Authors. Candida albicans has four chitin synthases from three different enzyme classes which deposit chitin in the cell wall, including at the polarized tips of growing buds and hyphae, and sites of septation. The two class I enzymes, Chs2 and Chs8, are responsible for most of the measurable chitin synthase activity in vitro, but their precise biological functions in vivo remain obscure. In this work, detailed phenotypic analyses of a chs2δ. chs8δ mutant have shown that C. albicans class I chitin synthases promote cell integrity during early polarized growth in yeast and hyphal cells. This was supported by live cell imaging of YFP-tagged versions of the class I chitin synthases which revealed that Chs2-YFP was localized at sites of polarized growth. Furthermore, a unique and dynamic pattern of localization of the class I enzymes at septa of yeast and hyphae was revealed. Phosphorylation of Chs2 on the serine at position 222 was shown to regulate the amount of Chs2 that is localized to sites of polarized growth and septation. Independently from this post-translational modification, specific cell wall stresses were also shown to regulate the amount of Chs2 that localizes to specific sites in cells, and this was linked to the ability of the class I enzymes to reinforce cell wall integrity during early polarized growth in the presence of these stresses.